Tax-Transfer Policy and Labor-Market Outcomes - Eissa, Nada; Nichols, Austin (American Economic Review, 2005)
Public policy towards low-income families with children in the United States has changed dramatically in the last two decades. The Aid to Families with Dependent Children (AFDC) program, in existence since 1935, was replaced with Temporary Assistance to Needy Families (TANF) as part of the 1996 Personal Responsibility and Work Opportunity Reconciliation Act (PRWORA). PRWORA eliminated the entitlement feature of cash assistance to poor families. Alongside this dismantling of the traditional welfare system has been the increasing reliance on the tax system as a means of providing cash support for needy families. A series of tax acts starting with the 1986 Tax Reform Act have increased assistance to the working poor through expansions of the Earned Income Tax Credit (EITC). In 2003, more than 21 million families are estimated to have benefited from the tax credit, at a total cost to the federal government of more than 37 billion dollars (U.S. Treasury 2004).1 It is widely accepted that the Earned Income Tax Credit (EITC) raised the employment of eligible women with children. Empirical evidence consistent with economic theory suggests that the EITC has been especially successful at promoting employment among eligible unmarried women with children (Eissa and Liebman 1996, Meyer and Rosenbaum 2000). In fact, the labor force participation rate of single mothers increased by an astounding 14 percentage points between 1989 and 2002, a period of substantial